2022
DOI: 10.18176/jiaci.0737
|View full text |Cite
|
Sign up to set email alerts
|

Patients With Atopic Dermatitis Sensitized to Pet Dander Mount IgE and T-Cell Responses to Mammalian Cystatins, Including the Human Self-Protein

Abstract: Background: Immediate as well as delayed-type hypersensitivity immune reactions to pet-borne allergens are commonly observed in atopic diseases. Further on in atopic dermatitis (AD), cross-reactivity to self-proteins is discussed to contribute to the disease. Human cystatin A and the cat allergen Fel d 3 belong to the cystatin family, an evolutionary conserved protein family. The objective of the present study was to assess cross-reactivity between mammalian cystatins and to analyze T cell responses to cystati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Nevertheless, these results might also indicate a need for the identification of new molecular allergens to which current non‐sensitized individuals might be sensitized 16,24 . Two new dog allergen molecules, Can f 7 and Can f 8, have been recently identified and added to the WHO/IUIS Allergen Nomenclature database, after the analyses in our study and the study by Käck and colleagues were performed 18,39,40 . Another explanation could be the presence of α‐Gal in cat and dog dander extracts 41 .…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Nevertheless, these results might also indicate a need for the identification of new molecular allergens to which current non‐sensitized individuals might be sensitized 16,24 . Two new dog allergen molecules, Can f 7 and Can f 8, have been recently identified and added to the WHO/IUIS Allergen Nomenclature database, after the analyses in our study and the study by Käck and colleagues were performed 18,39,40 . Another explanation could be the presence of α‐Gal in cat and dog dander extracts 41 .…”
Section: Discussionmentioning
confidence: 75%
“… 16 , 24 Two new dog allergen molecules, Can f 7 and Can f 8, have been recently identified and added to the WHO/IUIS Allergen Nomenclature database, after the analyses in our study and the study by Käck and colleagues were performed. 18 , 39 , 40 Another explanation could be the presence of α‐Gal in cat and dog dander extracts. 41 Kiewiet et al, 42 in a recent study of patients with α‐Gal syndrome, found a high frequency of sensitization to both dog and cat extracts but a low frequency of genuine cat and dog sensitization using CRD.…”
Section: Discussionmentioning
confidence: 99%
“…These autoantigens may then be processed by antigen presenting cells and presented to lymphocytes resulting in the production of IgG and/or IgE AAb by plasma cells 105 . IgE‐mediated autoimmunity in AD may also be caused by molecular mimicry due to cross‐reactive peptides between environmental antigens or skin microbiome and self‐antigens 91,106–108 . In addition, skin residing CD8 + cytotoxic T cells with intermediate affinity to self‐peptides may contribute to skin damage, and unconventional γδ T cells may also accumulate in the skin 109,110 .…”
Section: Autoreactive Ige In Atopic Dermatitismentioning
confidence: 99%
“…105 IgE-mediated autoimmunity in AD may also be caused by molecular mimicry due to cross-reactive peptides between environmental antigens or skin microbiome and self-antigens. 91,[106][107][108] In addition, skin residing CD8 + cytotoxic T cells with intermediate affinity to self-peptides may contribute to skin damage, and unconventional γδ T cells may also accumulate in the skin. 109,110 Finally, an extraordinary unspecific activation of the T and B cells might also underlie the response due to the conditions of an ongoing inflammation.…”
Section: Autore Ac Tive I G E In Atopi C Dermatitismentioning
confidence: 99%
“…These autoantigens may then be processed by antigen presenting cells and presented to lymphocytes resulting in the production of IgG and/or IgE AAb by plasma cells 103 . IgE-mediated autoimmunity in AD may also be caused by molecular mimicry due to cross-reactive peptides between environmental antigens or skin microbiome and self-antigens 89,[104][105][106] . In addition, skin residing CD8 + cytotoxic T cells with intermediate affinity to selfpeptides may contribute to skin damage, and unconventional γδ T cells may also accumulate in the skin 107,108 .…”
Section: Introductionmentioning
confidence: 99%